P04.18 Management of diffuse gliomas using hypnosis-aided awake surgery: oncological and functional preliminary results in a series of 16 cases. (6th September 2019) - Picart, T; Pardey Bracho, G; Ameli, R; Berner, L; Thomas, L; Cartalat, S; Honnorat, J; Ducray, F; Guyotat, J
Abstract: BACKGROUND: Awake resection of diffuse gliomas aims to find a tailored onco-functional balance for each patient. Hypnosis represents an innovative technique able to optimize the comfort and well-being of the patient during such procedures. The aim of the present study is to analyse the oncological and functional outcome in a cohort of patients operated on with hypnosis-aided awake surgery. MATERIAL AND METHODS: All consecutive adult patients that underwent hypnosis-aided resection for a diffuse glioma between January 2018 and January 2019 were recorded. Neurological and cognitive status were assessed preoperatively and at 3 months postoperatively. Extent of tumor resection was quantified by a radiologist on magnetic resonance imaging. RESULTS: Sixteen patients (6 males and 10 females), with a mean age of 39 years, were included. Gliomas were revealed by epileptic seizures (62.5%), motor deficit (6.25%) or incidentally discovered (31.25%) and were either located in the right hemisphere (50%) or in the left hemisphere (50%), with a mean initial volume of 42 mL. Histologically, there were six grade II-astrocytomas, three grade III-astrocytomas, five grade II-oligodendroglioma, one grade III-oligodendroglioma and one ganglioglioma. Under HAS, the awake-time after the anaesthesia drugs stop was short, because low doses of drugs were required thanks to the hypnotic state. All patients were able to reliably performed the different tests until functional subcortical limits were reached. Postoperative magnetic resonance imaging showed complete resection in 8 cases (50%), subtotal resection in 2 cases (12.5%) and partial resection in 6 cases (37.5%), with a mean resection rate of 84.6%. At 3 months after surgery, there was only a new motor deficit (6.25%). The language and neuropsychological assessments were improved in 7 patients (43.75%), stable in 7 patients (43.75%) and deteriorated in some tests in 2 patients (12.5%). After surgery, no patient reported negative emotion concerning the awake glioma resection and all patient declared being ready for a second awake resection in the future, if indicated. CONCLUSION: According to these preliminary results, hypnosis-aided awake resection of diffuse gliomas appears to be safe and effective from an onco-functional viewpoint and parallelly contributes to decrease intra-operative pain, anxiety and major discomfort.